Connecting Biodiversity With Mental Health and Wellbeing — A Review of Methods and Disciplinary Perspectives - Hedin, Madeleine; Hahs, Amy K.; Mata, Luis; Lee, Kate (Frontiers in Ecology and Evolution, 2022)
Biodiversity conservation and mental health and wellbeing are of increasing global concern, with growing relevance to planning and policy. A growing body of literature exploring the relationships between biodiversity and mental health and wellbeing - based on early research conducted largely from social science perspectives - suggests that particular qualities within natural environments confer particular benefits. Results so far have been inconclusive and inconsistent, contributing to an incohesive body of evidence. While past reviews have focussed on reporting variations in results, the present study builds on early reviews by exploring variations from the perspective of author disciplines and the use of different guiding theories, and variables used to measure biodiversity, mental health and wellbeing. This aims to address a research gap in understanding whether research in this topic has become more interdisciplinary or has employed more consistent study designs, which were highlighted as priorities in past reviews, but the progress of which has not yet been explored in depth. We found that research connecting biodiversity and mental health and wellbeing has become only marginally more interdisciplinary in recent years, and there is still a large inconsistency in the use of guiding theories, variables and overall study designs. The variation in disciplinary perspectives and methods reflects a growing interest in this field and the variety of ways researchers are trying to understand and test the complex relationships between biodiversity and mental health and wellbeing. Our study shows that there are unique perspectives that different disciplines can contribute to this body of research and continuing to increase collaboration between disciplines with the use of consistent mixed methods approaches in future may contribute to a more cohesive body of evidence. We provide a framework to conceptualise recommendations for future research, highlighting the importance of interdisciplinary collaboration at multiple scales, and importantly focusing on more specific, mechanistic studies to inform decision-making that provides co-benefits for biodiversity and mental health and wellbeing.